EVALUASI KEMAMPUAN TRANSFORMATOR DAYA PADA GARDU INDUK 150 KV WATES - Muhammad Suyanto; Ridwan Setyowibowo; Prasetyono Eko Pambudi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
Increased population growth, economy and insfrastructure development, especially the construction of airports in Kulon Progo district indirectly impact on power availability. An Increase electric load in each year will affect the capacity of the power transformer at the 150 KV Wates substasion. With increasing electric load it will be the greater the electrical load borne by teh power transformator, so to prevent the occurence of overload, it is necesarry to eavaluate the power transformer capability by doing electric load prediction. In this reseacrh, the method used is trend analysis. For power transformer-I use exponential trend with MAPE value of 2,91% obtained estimate of load in year 2019 equal to 25,74 MVA where loading already exceed 80% While power transformer-II using the quadratic trend with MAPE of 1,19% obtained by the estimated load in 2025 of 52,29 MVA, after the addition of a special load plan, obtained load estimation in 2019 has reached 80%. So that in the year 2019 has been done addition of new power transformer, and in year 2024 can be done uprating on power transformer-I.